History of personal computers in Japan. Issue 2 (3rd March 2020) - Yamashita, Ryozo
Abstract : We give a survey on the history of computers in Japan that have been produced over the last 50 years. Here, we focus on the topics of personal computers (PCs). We can see PCs produced in Japan have very unique features. They coevolved with some other related machines, e.g. word processing machines, game machines, etc. They also had several localised features such as capability of dealing with Japanese language. At the same time, developers of PCs struggled to find a good solution between localisation and globalisation. In the early stage of the history of PCs, their architectures were all different, and software had to be developed and tuned for each of them. Thus providing a common platform to all PCs on which every software can run was indispensable for globalisation. In this paper, how PCs in Japan have been evolved and how such problems were attacked are discussed based on the author's experiences of developing early PCs. GRAPHICAL ABSTRACT: